Ecologic relationships among host fruits, frugivorous flies and parasitoids in a fragment of tropical dry forest - Saavedra-Díaz, Jeferson; Galeano-Olaya, Pedro Edgar; Canal D., Nelson Augusto (Revista de Ciencias Agrícolas, 2017)
Fruit flies (Tephritoidea: Tephritidae and Lonchaeidae) are one of the main worldwide pests of fruits. The knowledge of the interactions among frugivorous flies with their host plants and parasitoids is necessary to develop integrated pest management programs. The aim of this study was to describe the tritrophics relationship (host plants, frugivorous flies and parasitoids) in a patch of dry tropical forest in the Centro Universitario Regional del Norte, Armero-Guayabal, Tolima, Colombia. Fruits of 35 different plant species were collected. The fruits were transported to the laboratory and were disposed individually for subsequent pupation and the emergence of flies and / or parasitoids. 2,940 larvae were recovered from fruits of 15 plant species; adults of six species of Tephritidae (five Anastrepha and Toxotrypana curvicauda) and eight of Lonchaeidae (six Neosilba and two Lonchaea) were obtained. Tephritids were the most abundant and caused the highest percentages of damage (0 to 83.31%) and infestation rates (0 to 10.32 larvae / fruit and 0 to 463.37 larvae/kg fruit), and Lonchaeids were the most polyphagous, infesting 12 host plants. Both families shared hosts. Sympatric species of Anastrepha neither share their host plants nor cohabit the same fruit; Neosilba species share hosts and fruits. Five species of parasitoids were collected. New records and associations of host plants, frugivorous flies and parasitoids are presented for Colombia.